Detection of Organic Contaminants in Water Based on Polysulfone Microspheres with Hollow Core/Porous Shell Structure - Li, Xianhua; Guo, Yongcun; Zhang, Jun (Asian Journal of Chemistry, 2013)
The monodisperse polysulfone microspheres with hollow core/porous shell structure were prepared using a water-in-oil-in-water (W/O/W) emulsion solvent evaporation technique. The morphology could be controlled by varying the type of surfactant such as oleic acid, poly(vinylpyrrolidone) and Tween 80, respectively. The prepared microspheres are developed as reagent for the detection of 1-methyl-2-pyrrolidinone , which is based upon the morphology changes of microspheres to 1-methyl-2-pyrrolidinone . Results show that the microspheres with hollow core/porous shell structure have an ultra sensitive response (as low as 10-7 M).